Pandangan Muhammad Asad tentang Shariah - ahmad nabil amir (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2019)
Abstrak: This paper analyzed Muhammad Asad’s views on Shariah (Islamic law). This was investigated from his thoughtful and broad understanding of its principle and underlying purpose. The essential understanding of the principle of shariah was analytically discussed in his works such as This Law of Ours and Other Essays, The Principles of State and Government in Islam and in his magnum opus The Message of the Qur’an. The finding shows that Muhammad Asad’s discussion on shariah emphasized on its dynamic principle and relevance to contemporary practice and modern context of Islam. It set forth important framework towards reforming Islamic law by critically reconstructing and reprojecting its ideal in order to establish justice in implementing the law and in framing the ideal that underlie its purpose.